2002
DOI: 10.1128/jcm.40.10.3596-3601.2002
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Persistence of Gonococcal DNA Detected by Ligase Chain Reaction in Men and Women following Recommended Therapy for Uncomplicated Gonorrhea

Abstract: Neisseria gonorrhoeae infection remains relatively common in the United States, representing a public health challenge. Ligase chain reaction (LCR) is both highly sensitive and specific for the detection of N. gonorrhoeae in urine and patient-obtained vaginal swab specimens. Because of the LCR test's exquisite sensitivity, it may potentially detect DNA from nonviable organisms following effective therapy, leading to false-positive test results and unnecessary additional treatment. The purpose of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…This result was not surprising because highly sensitive molecular tests for other organisms like pathogenic Neisseria and Chlamydia can sometimes detect nucleic acids from nonviable organisms for days to weeks after effective treatment. 43,44 We analyzed the clinical trial data using two published models to estimate the number of infected hepatocytes and average parasite burden in challenged non-immune volunteers. 42,45 These models are applicable to our trial because our study and the initial modeling studies used infection by five mosquitoes and achieved comparable times to both 18S rRNA and thick blood smear positivity.…”
Section: Resultsmentioning
confidence: 99%
“…This result was not surprising because highly sensitive molecular tests for other organisms like pathogenic Neisseria and Chlamydia can sometimes detect nucleic acids from nonviable organisms for days to weeks after effective treatment. 43,44 We analyzed the clinical trial data using two published models to estimate the number of infected hepatocytes and average parasite burden in challenged non-immune volunteers. 42,45 These models are applicable to our trial because our study and the initial modeling studies used infection by five mosquitoes and achieved comparable times to both 18S rRNA and thick blood smear positivity.…”
Section: Resultsmentioning
confidence: 99%
“…19,36,43,44 This problem has been due to limited sequencing of equivalent genes in commensal Neisseria species and the overall great homology between most Neisseria species. Recent work on sequencing of the entire porA pseudogene in N. gonorrhoeae 34 has facilitated the discovery of this gene as a promising target for highly sensitive and specific molecular diagnostics of N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that after successful therapy for gonorrhea, NAATs continued to give positive results for several days, but gonococcal DNA was cleared from urogenital specimens within 2 weeks. 45 Certainly, support for such concerns has been found in studies investigating NAAT testing for chlamydia. In fact, the Centers for Disease Control (CDC) recommend that a follow-up sample for NAAT testing should not be taken for at least 3 weeks after antibiotic treatment for chlamydia.…”
Section: Antibiotic Resistancementioning
confidence: 99%